Generational Bridges: Supporting Literacy Development With Elder Storytelling and Video Performance (LEARNing Landscapes, 2020)
This paper describes our implementation of digital storytelling within a First Nations community elementary school in eastern Canada. Our aim with this project was to support community engagement in the school, while promoting literacy development, by inviting Elders to share their stories, both traditional and modern lived experiences, with children in a grade 4/5 split class. Positioned as a participatory action research project, anchored in Indigenous methodologies, the project was developed through meetings with community members to build on the strengths of the community. Reflections from students illustrate that working with Elders gave deeper meaning to the stories they heard and performed, and fostered greater engagement in literacy development.
Keywords: digital storytelling; Elder engagement; literacy development; Indigenous pedagogy; performance literacy